The new way of controlling aluminum-doped zinc oxide films properties : ion beam post-treatment with cooling system - Ni, Zhengji (2013)
AZO thin films with low surface roughness and low sheet resistance are required in the touch panels and display panels. In this work, we investigated the substrate cooling effect of the ion beam post-treatment on AZO films properties, and one new way to obtain low surface roughness and low sheet resistance at the same time was proposed. The more exciting find of this paper is that, compared to the samples without cooling during the process of the ion beam post-treatment, samples with proper cooling voltage show a sheet resistance decrease of 26 % (from 11.9 Ω/□ to 8.8 Ω/□) and a roughness decrease of 35.5 % (from 13.389 nm to 8.637 nm) without transparency losing. And the viewpoint that substrate cooling has the effect of weakening the crystallization, especially for the subface and internal parts of samples is deduced.